A Guide to Confident Living - Norman Vincent Peale (Fireside Book, 2003)
"Dr. Peale helps you find the way to new energy that will actually revitalize your life. Here, he offers advice on how to: free your inner powers, "talk out" your troubles, lose your inferiority complex, achieve a calm center for your life, practice the power of prayer, find freedom from fear and sorrow, attain marital, professional, and personal happiness"--Publisher description.